Teaching the Arts in the Primary Curriculum - Ogier, Susan; Ogier, Susan; Tutchell, Suzy (SAGE Publications, 2021)
Learning in the arts does not fit in with simple, conventional methodologies for teaching and assessing in the traditional sense, but it has an immense power to transform children$1 (Bs understanding of the world around them, and their lives. Many jobs, currently and of the future, will demand the skills that learning in the arts will develop. This book brings Arts Education sharply into focus as a meaningful, learning experience for children of pre-school and primary age (3-11 years). It reinforces the potential for the wide range of physical, mental and emotional development, through learning opportunities that engagement in arts practice facilitates. Provides insight into how teachers can support children to consider contemporary challenges that face their generation. Includes expert voices from the world of education to demonstrate an expansive, and perhaps surprising, view of where and how the Arts can be found. Shows how we can bring the arts so easily into our curriculum, and into our classrooms.s